Recruitment of Brown Adipose Tissue as a Therapy for Obesity-Associated Diseases - FARMER, STEPHEN R.; Boss, Olivier (Frontiers in Endocrinology, 2012)
Brown adipose tissue (BAT) has been recognized for more than 20 years to play a key role in cold-induced non-shivering thermogenesis (CIT, NST), and body weight homeostasis in animals. BAT is a flexible tissue that can be recruited by stimuli (including small molecules in animals), and atrophies in the absence of a stimulus. In fact, the contribution of BAT (and UCP1) to resting metabolic rate and healthy body weight homeostasis in animals (rodents) is now well established. Many investigations have shown that resistance to obesity and associated disorders in various rodent models is due to increased BAT mass and the number of brown adipocytes or UCP1 expression in various depots. The recent discovery of active BAT in adult humans has rekindled the notion that BAT is a therapeutic target for combating obesity-related metabolic disorders. In this review, we highlight investigations performed in rodents that support the contention that activation of BAT formation and/or function in obese individuals is therapeutically powerful. We also propose that enhancement of brown adipocyte functions in white adipose tissue (WAT) will also regulate energy balance as well as reduce insulin resistance in obesity-associated inflammation in WAT.